Challenges of Dispute Settlement through International Court of Justice (ICJ): the Case of Ukraine v. Russian Federation, the Decision on Provisional Measures on Alleged Violation of Genocide Convention - Bezabh Abebe Bahiru (European Scientific Journal, ESJ, 2022)
This article aims to discuss the challenges faced by the International Court of Justice (ICJ) in the international dispute resolution processes by analyzing the case of Ukraine v. Russia emphasizing the decision of the court on the claims of provisional measures to stop the Russian military operation in Ukraine. To pinpoint the challenges faced by ICJ, the article uses a qualitative approach using both primary and secondary sources, however, the article stresses the latest pending case that Ukraine claims application for proceeding and provisional measures. It is obvious ICJ is the judicial organ of the UN however, the finding of this research shows that ICJ has been facing challenges and the problem is visible in Ukraine v. Russia pending case. Regardless of the marvelous effort state parties are quitting the jurisdiction of ICJ by rejecting the principle of international law of treaties. Such a move by the states like Russia damaged trust in the role of ICJ. Besides, the lacuna in the institutional independence in the process of election of judges has involved veto power of the Security Council which is a political organ. Even more, the election of ad hoc judges is based on motive of the national representation. To this effect, the verdict on claim of Ukraine’s provisional measure is decided by a split vote and the judges’ individual independence in decision-making power has been influenced by national interest, the political orientation of judges, ideology, and, diplomatic relations of states. However, the decision has failed to be enforced. The enforcement organ Security Council’s structural posture caused failure to execute decisions. Favoritism and intervention by unilateral sanction are also other problems. Therefore, the writer has concluded the court should deserve a radical change to preserve the intended object. The ICJ needs to empower independence from any organ of UN that would enhance its effectiveness. It is necessary to have a reform action plan to revise the election process of judges and presidents and the overall structural and functional capabilities of the court.